2020
DOI: 10.3390/pathogens9040254
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropathic Itch Caused by Pseudorabies Virus

Abstract: Pseudorabies virus (PRV) is an alphaherpesvirus related to varicella-zoster virus (VZV) and herpes simplex virus type 1 (HSV1). PRV is the causative agent of Aujeskzy’s disease in swine. PRV infects mucosal epithelium and the peripheral nervous system (PNS) of its host where it can establish a quiescent, latent infection. While the natural host of PRV is the swine, a broad spectrum of mammals, including rodents, cats, dogs, and cattle can be infected. Since the nineteenth century, PRV infection is known to cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 127 publications
2
60
0
Order By: Relevance
“…The confirmation of AD was made based on the real-time PCR and immunohistochemical results. The symptoms described in the present study were similar to those reported in the literature in cattle and were mainly characterized by neuropathic itch, considered a typical sign of AD in non-natural hosts [ 8 , 17 , 20 , 21 , 22 , 33 ]. Although the presence of itching may facilitate the diagnosis of AD, a differential diagnosis is required for psoroptic and sarcoptic mange and pediculosis.…”
Section: Discussionsupporting
confidence: 87%
“…The confirmation of AD was made based on the real-time PCR and immunohistochemical results. The symptoms described in the present study were similar to those reported in the literature in cattle and were mainly characterized by neuropathic itch, considered a typical sign of AD in non-natural hosts [ 8 , 17 , 20 , 21 , 22 , 33 ]. Although the presence of itching may facilitate the diagnosis of AD, a differential diagnosis is required for psoroptic and sarcoptic mange and pediculosis.…”
Section: Discussionsupporting
confidence: 87%
“…The confirmation of AD was made on the basis of the real time PCR and immunohistochemical results. The symptoms described in the present study were similar to those reported in literature in cattle and were mainly characterized by neuropathic itch, considered a typical sign of AD in non-natural hosts (Hutchcroft T. 1975;Hargemoser W.A et al1978;Matsuoka et al 1987;Anusuz Z. et al 1992;Fukusho A et al 1998;Laval and Enquist, 2020). Although the presence of itching may facilitate the diagnosis of AD, a differential diagnosis is required for psoroptic and sarcoptic mange, pediculosis .…”
Section: Discussionsupporting
confidence: 83%
“…In case of virus exposure through the oral, rectal and vaginal mucosa, pruritus typically develops in head, shoulder, flank, hind quarters and perineum (Hutchcroft T 1975;Hopp W. et al 1985), whereas, head and neck are mainly involved when infection occurs trough the nasal mucosa or respiratory tract (Down C. 1962;Hopp W. et al 1985.). The differential location of pruritus and pathological findings, suggest different distribution of the virus (Laval and Enquist, 2020). The pruritus indeed usually develops at the point of inoculation of the virus, reaching the related segment of the spinal cord from peripheric nerve termination.…”
Section: Discussionmentioning
confidence: 99%
“…New born and nursing pigs are most severely affected showing mortality rates of 100% and 50%, respectively. Respiratory and neurological signs (mad itch) in weaned pigs and abortions in pregnant sows are hallmarks of this disease [ 78 , 79 , 80 ]. Eradication of PrV in large parts of the world was feasible due to efficacious marker vaccines in combination with accurate differential diagnostic tools [ 81 ].…”
Section: Resultsmentioning
confidence: 99%